Factors affecting the effectiveness and safety of colistin in treating drug-resistant gram-negative bacterial infections: a meta-analysis - Li, Pengfei; Li, Shiran; Zhang, Jiao; Zeng, Siyu; Li, Zhimin; Xie, Jinxian; Yang, Yong (Frontiers in Pharmacology, 2025)
PurposeAs an important antibiotic for treating infections caused by drug-resistant Gram-negative bacteria, colistin’s clinical efficacy and safety might be influenced by multiple factors. This meta-analysis aimed to identify the key factors affecting the effectiveness and safety of colistin in treating these infections. The results of this study provide a reference for clinicians to choose treatment methods. At the same time, the rational use of colistin can prevent the occurrence of adverse drug reactions (AKI), improve the cure rate of patients, and delay the development of bacterial resistance.MethodsThe overall mortality rate was designated as the primary effectiveness outcome, with clinical response rate and bacterial eradication rate serving as the secondary outcomes. The incidence of acute kidney injury (AKI) was evaluated as a safety endpoint. Key analytical variables included colistin dose (high-dose≥4.2 mg/kg/day and low-dose< 4.2 mg/kg/day), ACCI (low <5, moderate = five to six, high >6), co-therapy (carbapenems/tigecycline/fosfomycin, etc.), microbial species (Acinetobacter baumannii/Pseudomonas aeruginosa/Enterobacteriaceae, etc.), and administration methods (aerosolized plus intravenous colistin vs. intravenous colistin alone).ResultsA total of 74 studies (N = 8,889 participants) were included in our analysis. Mortality was lower in the high-dose group compared to the low-dose group (34.09% vs. 41.08%, p = 0.09). In ACCI score subgroups (low, moderate, high), mortality rates were 27.11% vs. 44.69% vs. 47.11% (p < 0.01). Monotherapy was associated with a higher mortality rate compared to co-therapy (42.97% vs. 33.10%, p < 0.01). Although no statistical differences were observed among different pathogenic bacteria species, infection caused by A. baumannii exhibited the highest mortality rate at 43.75%. Mortality rates for aerosolized plus intravenous colistin versus intravenous colistin alone were 40.81% vs. 32.84% (p = 0.09). The incidence of AKI was significantly higher in the loading dose group, high-ACCI group, and group receiving concomitant nephrotoxic drugs while being notably lower in the Pseudomonas aeruginosa infection group.ConclusionLoading dose, co-therapy (carbapenems or quinolones), microbial factors, and ACCI are the main factors associated with the effectiveness of colistin. Additionally, loading dose, microbial factors, ACCI, and co-therapy are associated with an increased risk of colistin-associated AKI.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/search, identifier CRD420250655507.